Analisis Komplikasi Infeksi Terkait Tindakan Blok Epidural pada Pasien Pasca Operasi Di RSUD Dr. Zainoel Abidin Banda Aceh - Yusmalinda; Hafizh Arief; Zafrullah Khany Jasa (Journal of Medical Science, 2022)
Neuraxial block-associated infection is a rare complication, this could be due to better aseptic technique and possibility of unreported events. There are four mechanisms by which microorganisms enter the body during insertion of an epidural catheter, include inoculation of microorganisms on the skin surface, pathways along the insertion of epidural catheter, contamination of local anesthetic drugs, and hematogenous spread. The aim of the study is to find out incidence of infectious complications and risk factors for infection in patients who had an epidural catheter inserted in dr. Zainoel Abidin hospital Banda Aceh. A cross-sectional study was conducted over 3 months period with 45 total sampling patients who received epidural blocks. Analysis was done to know relationship beetwen age, number of attempts at insertion of epidural needles, duration of catheter in situ, comorbid DM, malignancy, duration of postoperative bed rest, and blood leukocyte count, signs of inflammation, neurological deficits, and bacterial culture of the epidural catheter. No infection was found, however there were 14 positive epidural catheter culture obtained Gram-negative rods. Nine of the 14 positive culture samples were patients with malignancy. All patients with positive culture samples had bed rest ≥2 days (p=0.004). No asociation between dependent and independent variables in this study (p>0.05). Positive culture results cannot be defined as an infection, however colonization at epidural catheter tip is an early sign of an imminent infectious process.